University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 1 - Section 1.6 - Inverse Functions and Logarithms - Exercises - Page 49: 53



Work Step by Step

To solve natural logarithm equations, keep in mind this property: - If $\ln x = \ln a$ then $x=a$ $$\ln (y-1)-\ln2=x+\ln x$$ - Condition: $y\gt1$ and $x\gt 0$ - Apply Quotient Rule to the left side: $$\ln\frac{y-1}{2}=x+\ln x$$ - For $x$, recall the property: $\ln e^x=x$ That means $$\ln\frac{y-1}{2}=\ln e^x+\ln x$$ - Apply Product Rule to the right side: $$\ln\frac{y-1}{2}=\ln xe^x$$ $$\frac{y-1}{2}=xe^x$$ $$y=2xe^x+1$$ *Reconsider the condtion: $y\gt 1$ means $2xe^x+1\gt1$ or $xe^x\gt0$ As stated above in the condition, we know that $x\gt0$. In addition, $e^x\gt0$ for all $x\in R$. Therefore, $xe^x\gt0$ for all $x$ in the defined range already.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.